Reaction of safflower breeding lines to Fusarium wilt: Reaction of safflower breeding lines to Fusarium wilt - SUMA MOKA; KADIRVEL PALCHAMY; R D PRASAD (Journal of Oilseeds Research, 2023)
Fusarium wilt (Fusarium oxysporum f. sp. carthami) is an important disease of safflower, causing 90% yield loss. The pathogen, being mainly soil-borne, is quite difficult to manage using conventional methods. Keeping this in view, the current study was conducted to identify the resistant breeding lines against wilt. A total of 30 multiparent cross-based breeding lines were screened in wilt sick pot and the results revealed that 29 lines were found immune, while one line showed a moderately susceptible reaction to wilt. These breeding lines can be further used in the resistance breeding programme to develop resistant varieties.